"Implicature-Laden" Elicitations in Talk Radio Shows - Herczeg-Deli, Ágnes (Research in Language, 2011)
Indirect elicitations in talk radio programmes on BBC Radio are not uncommon, notwithstanding, misunderstanding between the host and his conversational partner is not frequent. Investigating some of the reasons this paper focuses on how the socio-cultural and cognitive factors of the context interweave in discourse. The author suggests that valid interpretation and appropriate response to inferred elicitations can be best explained within the framework of Relevance Theory, and more specifically, with the presumption of accessibility of schemas obtained from the cognitive environment of the discourse partners. Through examples of empirical research the paper aims to reveal how the mutual knowledge of the participants controls discourse via the mental processes occurring in the interaction of two minds.